Kinetics of change of thickness of a lubricant layer at an operating time. - Дмитриченко, М.Ф.; Білякович, О.М.; Савчук, А.М.; Міланенко, О.А.; Туриця, Ю.О.; Кущ, О.І. (Problems of Tribology, 2015)
Dmitrichenko N.F., Bilyakovych O.N., Savchuk A.N., Milanenko A.A, Turitsa Y.A., Kusch A.I. Kinetics of change of thickness of a lubricant layer at an operating time.The working conditions of the lubricating oil in gear boxes are determined by three factors: temperature, rotation speed gears and the pressure in the contact zone. Of these factors depends on deploymentagent oil film in the contact mode and friction in tribomechanical system that determines the reliability and durability of the friction assembly. The range of pressures and velocities, which are implemented in the normal friction and wear of the surfaces defined by the nature of the materials contacting the vapor and the composition of the lubricant.The results of this work are presented based on experimental studies of the oil MGT oil and synthetic oil based polarpoint when using samples of steel 45 and SH-15. It is established that formed the boundary lubrication layer thickness 0,657 - 2,557 micrometer for MGT oil remains stable up to N  1000, then the degree of metallic contact is increased to 10 % of cycles, due to the changing nature of boundary films with increasing bulk oil temperature up to 50 °C. It is recorded that the increase in the thickness of the lubricant layer during start-up, regardless of the number of cycles at an operating time is about 1 - 1,2 micrometer, slightly affects the variation of the constant parameter mode lubricating action. Regardless of the type of lubricant is established linear correlation parameter of the efficiency of the lubrication of λ on the thickness of the boundary adsorption layers.